Admission Prevalence and Risk Factors of Deep Vein Thrombosis in Patients with Spinal Cord Injury Complicated with Cervical Fractures. (June 2022) - Lv, Bing; Wang, Haiying; Li, Weifeng; Han, Gefeng; Liu, Xiangdong; Zhang, Cheng; Zhang, Zipeng
The purpose of this study was to investigate the prevalence of deep vein thrombosis (DVT) and to clarify the risk factors of DVT in patients with acute spinal cord injury (SCI) complicated with cervical fractures at admission. From January 2018 to December 2021, a total of 175 patients with acute SCI complicated with cervical fractures in our hospital were retrospectively analyzed. Duplex ultrasound was used to diagnose the DVT. All patients' medical record data, including demographic variables, medical history, and laboratory results, were collected. The patients were divided into DVT group and non-DVT group according to ultrasound results. The prevalence of DVT was determined and risk factors of DVT were identified. Receiver operating characteristic (ROC) curve analysis was used to evaluate the diagnostic value of different factors. The prevalence of DVT at admission was 21.71%(38/175), including one (2.63%) with central DVT, thirty-two (84.21%) with peripheral DVT and five (13.16%) with mixed DVT. The multivariate analysis revealed that decreased lower extremity muscle strength, time from injury to admission, and D-dimer were risk factors for DVT at admission. The diagnostic value of D-dimer was the highest among these risk factors. In conclusion, in patients with acute SCI complicated with cervical fractures, the risk of DVT at admission is very high. Decreased lower extremity muscle strength, time from injury to admission, and D-dimer are risk factors for DVT. Moreover, D-dimer has the highest diagnostic value among these risk factors.